Taxonomic study of the angiosperm epiphytes of Belém, Pará, Brazil - Brito, Evellyn Garcia; de Sousa, Julio dos Santos; de Carvalho, Wendell Vilhena; Gurgel, Ely Simone Cajueiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
This study treats the taxonomy of the epiphytices angiosperms of Belém, Pará, including the analysis of botanical material originated from new collections and specimens from the Museum Goeldi (MG) and Agronomic Institute of the North (IAN) herbaria. Identification keys, descriptions, geographical distributions, comments, and illustrations of species are provided. In Belém the vascular epiphyte flora is represented by 6 families, 19 genera, and 22 species. Orchidaceae was the most representative family with 11 genera and 12 species. Codonanthe calcarata (Miq.) Hanst., Epiphyllum phyllanthus (L.) Haw., Notylia barkeri (Hook.) Lindl., and Orleanesia amazonica Barb. Rodr. are new records for Belém, and Aechmea aquilega (Salisb.) Griseb. is a new record for the state of Pará. The flower was the main character for separating species, and terra firme forest was the plant formation that had the highest occurrence of species.